Health peace happiness. - Goh, Shi Ting. (2009)
This report traces the journey that Roadtrip Studios took to complete the video documentary “Health, Peace, Happiness”. It first gives a brief insight on the pre-production research phase of shaping the story, style and treatment. The report then chronicles the two months where the team closely followed the last days of two cancer-ridden subjects. Due to the highly sensitive and emotional topic the team was tackling, there were many considerations during production where the team’s decision-making skills were put to the test. This report addresses them and traces the problem-solving process. Similarly post production posed several challenges with which the team grappled. Lastly, there will be an evaluation of the entire process of materializing the video documentary.